Elucidating the discursive landscape of sex work in Johannesburg, South Africa - Mbatha, Khonzi; Terre Blanche, Martin (PINS-Psychology in Society, 2021)
In discussions about sex work, two dominant views are evident: Sex workers freely choose to sell sex as a means of earning an income or sex workers are victims of circumstances, driven into the sex industry through coercion or dire poverty. Both these views oversimplify the actuality of sex work. Sex workers themselves also at times oscillate between these two positions, but in this article we demonstrate how they are able, to some extent, to open up discursive spaces between these two extremes. However, just as sex workers are neither entirely passive victims nor entirely free agents in their lived experience, so too they are neither entirely passive channels for larger social discourses about their profession, nor entirely free to voice an authentic, first-hand account of what sex work “really” is. To explore this discursive entanglement, we spoke to five sex workers in Johannesburg and describe the ways in which they were able to both take on board, and to challenge, a variety of different discourses in order to talk about themselves as simultaneously agentic and constrained in what they can do.